PERTANGUNGJAWABAN PIDANA DALAM KEADAAN DARURAT BENCANA COVID-19 - ERWIN UBWARIN; PATRICK CORPUTTY (Universitas Islam Kadiri, 2020)
The handling of non-natural disasters Covid-19 must be carried out quickly and appropriately, but the threat of capital punishment threatens, especially for policymakers, but on the other hand with such a large handling fund, of course, it raises the potential for acts of corruption. The purpose of this paper is to formulate the responsibility of a criminal act in a criminal act, the state is in a state of disaster Covid-19. The method used is juridical normative, the source of primary, secondary, and legal legal materials, the results of research conducted that criminal acts in the event of a disaster for the safety and welfare of many people cannot be held liable for criminal liability, and in article 27 paragraph 2 Government Regulation Substituting the Law Number 1 of 2020 is intended for policymakers not to commit acts against the law, with good intentions and in accordance with statutory regulations. The intention of good faith is that it does not fulfill the element of being against material law. Although the Constitutional Court Decision has overturned the nature of violating material law, the Supreme Court continues to apply the nature of violating material law both from negative and positive functions. Keywords: Criminal Acts, Disasters, Covid-19